2012
DOI: 10.2478/s11686-012-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the vitellarium in the digeneans Phyllodistomum angulatum (Plagiorchiida, Gorgoderidae) and Azygia lucii (Strigeida, Azygiidae)

Abstract: Fine structural features of the vitellarium of two digeneans, Phyllodistomum angulatum and Azygia lucii, are documented and compared with those of other digenean species. The cytodifferentiation of immature vitelline cells (vitellocytes) assumes the production and subsequent accumulation in their cytoplasm of several inclusions. Mature vitelline cells of P. angulatum are characterized by the presence of vitelline clusters (~2.7 μm in diameter, with ~100 vitelline globules of ~0.35 μm in diameter) and osmiophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…4 B). The same vitelline cytoarchitecture as occurs in the gorgoderids has also been found in the azygiid Azygia lucii by Poddubnaya et al (2012), in the fasciolid Fasciola hepatica by Irwin and Threadgold (1970) and Hanna (1976), in the paramphistomid Orthocoelium scoliocoelium by Sharma and Swarnakar (1992) and in the haploporid Haploporus lateralis by Sampour (2008). Finally, despite the small number of digenean species studied in relation to their vitelline cytoarchitecture, specific structural patterns of the vitellarium can be observed in certain digenean families or even superfamilies.…”
Section: Characteristics Of Another Type Of Vitelline Structure Withimentioning
confidence: 71%
See 3 more Smart Citations
“…4 B). The same vitelline cytoarchitecture as occurs in the gorgoderids has also been found in the azygiid Azygia lucii by Poddubnaya et al (2012), in the fasciolid Fasciola hepatica by Irwin and Threadgold (1970) and Hanna (1976), in the paramphistomid Orthocoelium scoliocoelium by Sharma and Swarnakar (1992) and in the haploporid Haploporus lateralis by Sampour (2008). Finally, despite the small number of digenean species studied in relation to their vitelline cytoarchitecture, specific structural patterns of the vitellarium can be observed in certain digenean families or even superfamilies.…”
Section: Characteristics Of Another Type Of Vitelline Structure Withimentioning
confidence: 71%
“…In the gorgoderids Gorgoderina vitelliloba (see Irwin & Maguire, 1979) and Phyllodistomum angulatum (see Poddubnaya et al, 2012) a different type of basic structure of the vitellarium is found. This includes the presence of: (1) two types of cells within the vitelline masses (vitellocytes and interstitial cells, the latter with the same cytomorphology); (2) intercellular septate junctions between the interstitial cells; and (3) a fibrous sheath surrounding the vitelline masses (Fig.…”
Section: Characteristics Of Another Type Of Vitelline Structure Withimentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrastructural characters of the vitellarium might be useful .... for a better understanding of the relationships between different taxa within the neoophoran Platyhelminthes (Gremini & Falleni, 1998) including Cestoda (Świderski & Mackiewicz, 1976;Świderski & Xylander, 2000;Bruňanská et al, 2005;Poddubnaya et al, 2006Poddubnaya et al, , 2012Levron et al, 2007). The structure and composition of eggshell-forming globules in vitellocytes have been considered to be especially phylogenetically informative (Gremigni & Falleni, 1991;Falleni et al, 2001).…”
Section: Introductionmentioning
confidence: 99%